(3GdEbJUGO GdfbOj hGdOhdjs - (3CMeO aQjO(B, (3eUWais ((3GdGScfOQjI(B:s (3eDSSI THGH GdLGeYI(B,s, 2009)
(3GdEbJUGO GdfbOj(B-(3GdfbhO,CTcGdgG GdJGQNjI hJWhQgG (B-(3WHjYI GdfbhO heGgjJgG (B-(3GdhXGFa GdEbJUGOjI ddfbhO (B-(3GdJbSje GdfhYj ddfbhO (B-(3CKQ GdfbhO Ydi GdeJZjQGJ GdEbJUGOjI (B-(3GdfjhcdGSjc hGdWdH Ydi GdfbhO(B((3JMdjd ejdJhf aQjOeGf(B) -(3GdJMdjd GdfbOj GdeYGUQ dOGdI GdWdH Ydi GdfbhO (B-(3GdYhGed GdeMOOI dcejI GdfbhO (B-(3GdefGgL hGdfXQjGJ GdeNJdaI ddJhGRf GdEbJUGOj (B-(3feGPL GdJhRGRf(B((3JMdjd cdj(B) -(3GdCfXeI hGdSjGSGJ GdfbOjI (B-(3GdLgGR GdeUQaj (B-(3Shb GdeGd(B((3HhQUI GdChQGb GdeGdjI(B) -(3GdEbJUGO GdOhdj(B:(3fXQjI GdJLGQI GdOhdjI (B-(3ejRGf GdeOahYGJ (B-(3SYQ GdUQa (B-(3JhGRf ejRGf GdeOahYGJ (B-(3eYOd GdJHGOd GdOhdj (B-(3GdSjGSI GdJLGQjI heTcdI GdHdGO GdfGejI (B-(3GdLGJ hLhdI hChQLhGjs
(3GdeQGLY U(B.491 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3EbJUGO(B- (3fbhOs; (3GdCShGb GdeGdjIs; (3GdEbJUGO GdOhdjs; (3GdJLGQI GdNGQLjIs